Avaliação da interação do cobre com o óxido de grafeno empregando a técnica de fluorescência molecular e modelos matemáticos - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The contamination of water by heavy metals such as copper has been the subject of many studies in recent years, due to the increased concentrations of this metal in the environment due to the high mobilization to fresh water through soils, and residues from human activities. such as mining, industry and agriculture. Thus, it is essential to develop efficient methods, techniques and materials for applications in treatments, remediation, sensing and detection of pollutants. Carbon nanomaterials have gradually gained the center of attention, especially materials based on graphene such as graphene oxide (GO), which has unique properties and has interesting functional groups for environmental applications. Based on this, the present study sought to evaluate the capacity of graphene oxide to bind through chemical complexation to copper metal, in order to identify and understand the mechanisms involved in these interactions. For this, the molecular fluorescence technique was associated with the mathematical models of Ryan and Weber and that of Stern-Volmer. As a result, the GO showed fluorescence in the visible region, with maximum intensity for λem = 450 nm and λexc = 520 nm. The suppression of the fluorescence signal was monitored by titrating the GO solution with increasing concentrations of Cu²⁺, and it was possible to notice a gradual attenuation in the intensity values according to the increase in copper concentrations, as a result of the interaction of copper with conjugated and aromatic structures, as well as oxygencontaining groups. The mathematical modeling that best fitted the intensities was that of Ryan and Weber, and this is due to the non-linear adjustment. This same model, showed a very good interaction of GO with the metal ion, due to the values of Log K = 3,19 and CL of 5,93x10-5 mol L-1 , besides that, from the value of 38,1 fluorescence has not decreased further, proving the complexing capacity of copper with the available binding sites for the interaction of graphene oxide. Thus, the GO can have an efficient approach to interact with metals and can be a new tool for remediation of areas contaminated by copper ions.
Keywords: Supressão de fluorescência; Óxido de grafeno; Cobre; Interações moleculares; Suppression of fluorescence; Graphene oxide; Metal; Copper; Molecular interactions; CNPQ::ENGENHARIAS